Mitochondria-targeting graphene oxide nanocomposites for fluorescence imaging-guided synergistic phototherapy of drug-resistant osteosarcoma - Zeng, Wei-Nan; Yu, Qiu-Ping; Wang, Duan; Liu, Jun-Li; Yang, Qing-Jun; Zhou, Zong-Ke; Zeng, Yi-Ping (Journal of nanobiotechnology, 2021)
Osteosarcoma (OS) is the most common primary malignant bone tumor occurring in children and young adults. Drug-resistant osteosarcoma often results in chemotherapy failure. Therefore, new treatments aimed at novel therapeutic targets are urgently needed for the treatment of drug-resistant osteosarcoma. Mitochondria-targeted phototherapy, i.e., synergistic photodynamic/photothermal therapy, has emerged as a highly promising strategy for treating drug-resistant tumors. This study proposed a new nano-drug delivery system based on near-infrared imaging and multifunctional graphene, which can target mitochondria and show synergistic phototherapy, with preferential accumulation in tumors. Based on our previous study, (4-carboxybutyl) triphenyl phosphonium bromide (TPP), a mitochondria-targeting ligand, was conjugated to indocyanine green (ICG)-loaded, polyethylenimine-modified PEGylated nanographene oxide sheets (TPP-PPG@ICG) to promote mitochondrial accumulation after cellular internalization. Thereafter, exposure to a single dose of near-infrared irradiation enabled synergistic photodynamic and photothermal therapy, which simultaneously inhibited adenosine triphosphate synthesis and mitochondrial function. Induction of intrinsic apoptosis assisted in surmounting drug resistance and caused tumor cell death. After fluorescence imaging-guided synergistic phototherapy, the mitochondria-targeting, multifunctional graphene-based, drug-delivery system showed highly selective anticancer efficiency in vitro and in vivo, resulting in marked inhibition of tumor progression without noticeable toxicity in mice bearing doxorubicin-resistant MG63 tumor cells. The mitochondria-targeting TPP-PPG@ICG nanocomposite constitutes a new class of nanomedicine for fluorescence imaging-guided synergistic phototherapy and shows promise for treating drug-resistant osteosarcoma.